Public Confidence and Willingness of Report Crimes in Nigeria: The Submission of the Residents of Abeokuta South Local Government - Folorunsho Muyideen Ogunmefun; Onyeukwu Bruno Chibike (PT Keberlanjutan Strategis Indonesia, 2026)
In Nigeria, the several publications have decipher poor performance of the Nigerian Police through internal and external factors. However, this paper intends to inquiry into the willingness of the residents towards reporting crime to the Nigeria Police as expected. Extant literature were reviewed while instinctual drive theory was adopted for the explanation of the research inquiry. The study adopted Mixed (quantitative and qualitative) methods and cross sectional survey for collection of data from 256 residents of Abeokuta South Local Government area in seven (7) wards. Multistage was adopted was adopted to break the study locations to wards, streets and house numbers before purposive sampling method was adopted for the administration of the questionnaire face to face to the respondents. The Linear Regression analysis was adopted and the study found out that trust in police fairness (0.152. p=005), Openness in engagement (0.200, p=<005), Trust in police procedure (0.172, p=<005) Rights protection (0.138,p=<005) and Institutional commitment (0.127,p=005) were significant compared with other variable stated. The qualitative result corroborate with scholarly submission of the past indicating that lack of confidence and willingness to report crime stem from corrupt nature of the Nigeria Police and poor response to emergency as it occurs the study recommended that encouragement of confidentiality in crime reporting techniques, advocacy for transparency community support in policing, and continuity in whistle blowing reporting.